2004
DOI: 10.1592/phco.24.14.1323.43152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low‐Dose Valganciclovir for Prevention of Cytomegalovirus Disease in Renal Transplant Recipients: A Single‐Center, Retrospective Analysis

Abstract: A high rate of CMV disease was noted among the D+/R- population. Administration of ATG as an induction agent also increased the frequency of CMV disease. Despite the low dosage of valganciclovir, hematologic adverse events were common. However, valganciclovir, administered at 450 mg/day for 6 months, was effective and relatively safe for prophylaxis of CMV disease in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 22 publications
5
50
1
3
Order By: Relevance
“…Sun et al (28,32,38,(40)(41)(42)(43)(44)46,47,52,56 (28,31,32,35,37,38,40,(42)(43)(44)(45)(46)(47)50,51,56 (28,38,43,44).…”
Section: Risk Of CMV Disease With Prophylaxis a Total Of 2094 Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al (28,32,38,(40)(41)(42)(43)(44)46,47,52,56 (28,31,32,35,37,38,40,(42)(43)(44)(45)(46)(47)50,51,56 (28,38,43,44).…”
Section: Risk Of CMV Disease With Prophylaxis a Total Of 2094 Patientmentioning
confidence: 99%
“…In the 10 studies that considered ganciclovir-resistance, five assessed if resistant virus existed by clinical observation and none was documented (35,45,48,52,53 (42). In the remaining three studies (36,54,55), patients were assessed for ganciclovir-resistant CMV as clinical indicated and one patient had documented resistant virus (54).…”
Section: The Duration From Transplantation To Development Of Late-onsmentioning
confidence: 99%
“…Furthermore, literature evidence says incidence of thrombocytopenia with low-dose valganciclovir as prophylaxis for CMV infections in post-transplant patients was 24% and almost 20% of patients discontinued valganciclovir due to thrombocytopenia [8].…”
Section: Discussionmentioning
confidence: 99%
“…41 Gabardi and associates also concentrated on intermediate-risk patients (>80%) and concluded that valganciclovir administered at 450 mg/d for 6 months was effective and relatively safe for prophylaxis of CMV disease in kidney transplant recipients. 42 Emergence of CMV resistance is a major concern with low-dose valganciclovir, especially for high-risk patients. 18 Our study included intermediate-risk patients who had lower incidence of CMV infections and did not report any CMV resistance.…”
Section: Cytomegalovirus Diseasementioning
confidence: 99%